(untitled) (Texas Journal of Philology, Culture and History, 2024)
Translation plays a vital role in global communication by promoting cross-cultural understanding and facilitating effective communication between individuals from different language backgrounds. This article explores the significance of translation in fostering intercultural exchange and its impact on global communication. Cross-cultural understanding relies on the ability to access and comprehend diverse cultural perspectives, literary works, and intellectual contributions from around the world. Translation serves as a bridge, allowing for the dissemination of knowledge, ideas, and values across borders, fostering empathy and mutual respect.